Socio-Economic Priorities for the Sustainable Development of Russian Arctic Macro-Region - Leksin, Vladimir Nikolaevich; Porfiryev, Boris Nikolayevich (Economy of Regions, 2017)
To properly justify the priorities for the Russian Arctic Zone sustainable development is methodologically challenging for two reasons. Firstly, this challenge is due to fast changes of external and internal conditions for the development of the Arctic Zone of the Russian Federation (AZRF). Secondly, the interpretation of the concept of “sustainability” is too wide inconsistent. As the concepts of “sustainability” as well as the concept of “sustainable growth” in this wide sense are frequently used to characterize economic, social and other processes and systems, these key categories are difficult to apply as development’ targets and evaluation criteria practice of public administration in Russia. Using the case of Arctic macro-region, the paper substantiates the concept of spatial systems’ sustainability as their ability to maintain functionality under destabilizing impact of exogenous and endogenous factors. Such an ability is particularly important because of variations in structure and intensity of these negative impacts, including from climate change. Within this methodological framework, we have specified the indicators of sustainability relating to the practice of public management in the AZRF development. The paper has discussed the existing and emerging exogenous and endogenous impacts on the AZRF development sustainability. We set two priorities among the goals and objectives for ensuring the AZRF sustainable functioning under the conditions of climate. In social (socio-economic) sphere, it is necessary to maintain and improve the public health. In economic sphere, the most needed are strengthening of coherency and reliability of the transportation system, energy supplies to distant consumers, and stimulating of investment and industrial activities of the large industrial corporations.